MANAJEMEN LABA BERBASIS AKRUAL DAN RIIL SEBELUM DAN SETELAH KONVERGENSI IFRS PADA PERUSAHAAN MANUFAKTUR TERDAFTAR DI BEI - Ni Made Putri Utami; Endar Pituringsih; Biana Adha Inapty (InFestasi, 2016)
This study aims to provide empirical evidence on earnings management practices on manufacturing companies listed in Indonesian Stock Market before and after IFRS convergence (2007-2011). Accrual earnings management (the level of discretionary accruals) and real earnings management (abnormal cash flow from operation, abnormal production costs, and abnormal discretionary expenses) are observed to analyze earnings management practices. Data was retrieved using the purposive sampling method and tested with paired sample t-test and correlation test. The results empirically showed that there was no difference between accrual earnings management before and after the IFRS convergence. Additionally, real earnings management also showed that there was no difference between before and after the IFRS convergence. Other results also showed that there was no relationship between management interchangeable accrual earnings and real earnings management after convergence of IFRS. The implications of this research provided information to the users of financial statements, especially shareholders and investors to increase the awareness of the opportunities of accrual earnings management and real earnings management through manipulation of the cash flow, sales and production cost by management.